Accounting Strategy of a Company as a Factor in the Management of Business Value - SVETLANA V. Ponomareva (Учёт. Анализ. Аудит, 2019)
The article deals with the features of formation of the accounting strategy of the company as a factor in the management of business value. From the point of view of financial theory, the indicative financial strategy depends on the content of the account strategy, the adequacy of the company’s mission and the financial interests of the owners. Information of accounting, analysis and auditing should become the methodological basis for planning, budgeting and forward-looking strategies of money indicators, normative cost, economic analysis and internal control in competitive conditions and in case of the gradual lifting of the excessive companies (economically unjustified) legal restrictions of limitations on the choice of accounting policies and methods of evaluation indicators of financial statements.